Dukungan Sosial dari Rekan Kerja sebagai Prediktor Burnout pada Guru PAUD di Masa Pandemi COVID-19 - Gabriella Irena Carissa; Margaretha Purwanti (Universitas Kristen Maranatha, 2022)
Preschool teachers are one of the high-risk professions to experience burnout because of job demands. The teachers’ job demands increased during COVID-19, resulting in an increased risk of preschool teachers’ burnout. This study aimed to examine social support from colleague as predictor for preschool teachers’ burnout during pandemic COVID-19. The method used is quantitative and 121 preschools’ teacher from 7 provinces in Indonesia were recruited based on snowball sampling. There are two instruments in this research, the social support from colleague questionnaire and burnout questionnaire. All of the instruments are valid with the score 0.555 - 0.862 for social support from colleague questionnaire and 0.429 – 0.804 for burnout questionnaire. Reliability test with Alpha Cronbach indicate that all the instruments are reliable and the score are 0.964 and 0.973. The study result indicates that the contribution of social support in influencing burnout is 32,4%. This result is in line with previous study, however the influence of social support decreases from 58% to 32,4% because of pandemic COVID-19. During pandemic, the teachers work from of home most of the time and face-to-face interaction reduce to prevent spread of the virus. So, there is difficult to get social support from colleague. In the future, follow-up studies can gather more participants from all provinces in Indonesia and involve other factors which can affect the preschool teachers’ burnout.